2015
DOI: 10.1016/j.jdent.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Protein-repellent and antibacterial dental composite to inhibit biofilms and caries

Abstract: Objectives Biofilm acids contribute to secondary caries, which is a main reason for dental restoration failures. The objectives of this study were to: (1) develop a protein-repellent and antibacterial composite, and (2) investigate the effects of combining 2-methacryloyloxyethyl phosphorylcholine (MPC) with quaternary ammonium dimethylaminohexadecyl methacrylate (DMAHDM) on composite mechanical properties and biofilm response for the first time. Methods MPC, DMAHDM and glass particles were mixed into a denta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
109
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 61 publications
(129 reference statements)
4
109
0
4
Order By: Relevance
“…Recent studies have reported technological improvements in composite resin. Of particular interest are antibacterial additives that might reduce secondary caries and biofilms and enhance remineralization of teeth (29)(30)(31). Thus, material-induced reactions should be expected when margins beyond the CEJ are required.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported technological improvements in composite resin. Of particular interest are antibacterial additives that might reduce secondary caries and biofilms and enhance remineralization of teeth (29)(30)(31). Thus, material-induced reactions should be expected when margins beyond the CEJ are required.…”
Section: Discussionmentioning
confidence: 99%
“…Disks with 2-day biofilms were transferred into tubes with 2 mL of CPW, and the biofilms were harvested by sonication and vortexing [35,36]. Three types of agar plates were prepared.…”
Section: Colony-forming Unit (Cfu) Countsmentioning
confidence: 99%
“…glass fillers (referred to as "EBPM+NACP+MPC"); MPC mass fraction in the composite was 3% because a previous study showed that this yielded a strong protein-repellent property without compromising mechanical properties [36].…”
Section: Development Of Protein-repellent Antibacterial and Rechargementioning
confidence: 99%
See 2 more Smart Citations